Slang Words Used by Millennials in Pekalongan (Universitas Negeri Semarang, 2022)
One of the phenomena in millennial era is a slang language. It is not based on the standard language, but it is used as a daily language among the particular community. This article aims to find the slang language used by the millinneals in Pekalongan, describe the structure of words and interpret its meaning. The method used in this study was descriptive quality. The object was the millennials living in Pekalongan. The instrument in this article was a questionnaire. The step in technique of analyzing the data was to record the information that had been obtained, spread the structure of the slang language and interpret the meaning. The researcher found that the form of word formation process used in slang word by millenials were blend, acronym, loan words, clipping, and extreme internal change. Based on the analysis, the word blend is coming from the combination of all Indonesian word. All of the acronyms found were from English sentences or phrases. The loan words were borrowing from Javanese and English, but most of the loan words were borrowed from English. The meaning of slang words could be interpreted from the conceptual meaning of the elements that made up the words itself.